PENDAMPINGAN SALAT DHUHA DAN SALAT DHUHUR BERJAMAAH UNTUK PEMBIASAAN DIRI DI SMK DARUL ULUM PURWODADI - Wiwin Fachrudin Yusuf; Askhabul Kirom; Yusti Aulia Wuni; Lailatus Syarifah; Khoirotun Nafisatul M; Aning Agustyarini (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2023)
In times like this, there are still many young people who ignore morals or commendable behavior towards themselves, other people and the environment in which they are. Seeing incidents like that the school should also take part in improving the attitude and mentality of their students because this is also a link in the learning process. Knowing about such things at the school we met, namely SMK Darul Ulum Purwodadi, handled it by deepening their religious knowledge by disciplining Duha and Dhuhur prayers in congregation every day. The goal in this case is to accompany Duha prayers and congregational Dhuhur prayers for self-accustoming at Darul Ulum Purwodadi Vocational School. The method of implementing the activity is using the PAR (participatory action research) method. The results of the activity show that 90% of this habituation has been very successful in its application, so that students are able to get used to thinking, behaving, and acting in accordance with the teachings of Islam.